2018
DOI: 10.4081/cp.2018.1085
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Juvenile Psammomatoid Ossifying Fibroma with Secondary Aneurysmal Bone Cyst of the Maxilla: A Case Report and Review of Literature

Abstract: Juvenile ossifying fibroma is a benign fibro-osseous lesion commonly affecting the extra-gnathic craniofacial skeleton of the young individuals. The psammomatoid and trabecular variants are its two histopathological subtypes having distinctive clinico-pathological characteristics. Secondary aneurysmal bone cysts are frequently reported to arise in the pre-existing fibro-osseous lesions but rarely reported in the psammmomatoid variant of the juvenile ossifying fibroma. Such hybrid lesions, especially massive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
4
Order By: Relevance
“…The mean age of occurrence JPSOF is approximately 20 years whereas in case of JTOF, the mean age of occurence is 81/2 to 12 years suggesting JTOF is more common in children and adolescents. In the current case the patient was 15 yrs considering the age of the patient it is more in favour of JTOF however literature review ( 8 , 9 ) reports that JPSOF have been observed in patients as young as three months and as old as seventy two years and the present case is a classic example of this wide age range of JPSOF as the patient was 15yrs which is the age more common for JTOF.…”
Section: Discussionmentioning
confidence: 55%
“…The mean age of occurrence JPSOF is approximately 20 years whereas in case of JTOF, the mean age of occurence is 81/2 to 12 years suggesting JTOF is more common in children and adolescents. In the current case the patient was 15 yrs considering the age of the patient it is more in favour of JTOF however literature review ( 8 , 9 ) reports that JPSOF have been observed in patients as young as three months and as old as seventy two years and the present case is a classic example of this wide age range of JPSOF as the patient was 15yrs which is the age more common for JTOF.…”
Section: Discussionmentioning
confidence: 55%
“…FD, OF, and cementoosseous dysplasia are the noted BFOLs. [14] e recent World Health Organization classification of head and neck tumors in 2017 described four fibro-osseous lesions: OF, FD, familial gigantiform cementoma (FGC), and cemento-osseous dysplasia. [2,5,8,9,13] OFs are benign fibro-osseous neoplasms affecting the craniofacial skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Simple curettage or excision will not disconnect the blood supply nor correct the displacement of vessels which logically leads to a second expansion. Pedwa et al ( 17 ), Trent et al ( 13 ), Sarode et al ( 32 ) and Gotmare et al ( 33 ) all reported JABCs with initial curettage treatment then followed by recurrence and a second thorough hemi-mandibulectomy or maxillectomy were needed. Reddy et al ( 25 ) also presented a relapse case in which this patient had taken over a second curettage along with cryotherapy.…”
Section: Discussionmentioning
confidence: 99%